Optical properties, structural parameters, and bonding of highly textured rocksalt tantalum nitride films - Matenoglou, G. M.; Lekka, Christina E.; Koutsokeras, Loukas E.; Abadias, Gregory; Camelio, S.; Evangelakis, Georgios Antomiou; Kosmidis, C.; Patsalas, Panos A. (My University, 2008)
Tantalum nitride is an interesting solid with exceptional properties and it might be considered as a representative model system of the d3s2 transition metal nitrides. In this work highly textured, stoichiometric, rocksalt TaN(111) films have been grown on Si(100) by pulsed laser deposition. The films were under a triaxial stress, which has been determined by the sin2 ψ method. The stress-free lattice parameter was found to be 0.433±0.001 nm, a value which has been also determined by ab initio calculations within the local spin density approximation. The optical properties of TaN have been studied using spectroscopic ellipsometry and detailed band structure calculations. The electron conductivity of TaN is due to the Ta 5dt2g band that intercepts the Fermi level and is the source of intraband absorption. The plasma energies of fully dense rocksalt TaN were found to be 9.45 and 9.7 eV based on the experimental results and ab initio calculations, respectively. Additional optical absorption bands were also observed around 1.9 and 7.3 eV and attributed to be due to crystal field splitting of the Ta 5d band (t2g→eg transition) and the N p→Ta d interband transition, respectively
Keywords: Physics; Tantalum; Absorption; Pulsed laser applications; Tanning; Transition metals